Objetos de aprendizagem nos anos iniciais do ensino fundamental : limites e possibilidades no letramento de alunos de uma escola particular de Porto Alegre - Lázaro, Fernando Vieira (2017)
This Master´s dissertation analyzed the role of digital learning objects in the process of acquisition and promotion of reading of students of the 3rd year of Elementary School. In order to proceed with the investigation, documentary research and interviews with teachers were used as a data collection tool. The methodological approach is qualitative, with the application of the Case Study. The interviews and document examination converge to meet the objectives proposed in the research: to investigate the criteria adopted for the selection of learning objects and to analyze how teachers organize pedagogical practices according to the stages of literacy. As results, the pedagogical practices of digital literacy proposed by teachers, which related to learning objects support teaching and learning, were listed. In this way, from the identification of the practices it was possible to understand how these resources were selected by the teachers (criteria) and what practices are associated with them. In response to the research, the training of teachers does not depend on specific courses in the technology area, since the researched school has specialized teams in Information Technology, suitable for the preparation of equipment and for the instruction of teachers. After learning about the procedures for dealing with learning support, this information can be multiplied to other teachers. With the information available to all, the pupils' level of digital literacy is high and allows them to even help teachers, and this factor contributes to the student's involvement and can suggest solutions to simplify the use of Devices. On the different ways of learning and teaching, teachers agree on the gap between the period in which they have learned to teach and the current technological scenario. There have been changes that need to be monitored and for the innovations to work, one needs to get used to the digital resources.